The Influence of Social Media Exposure and Online Emotional Intimacy on the Likelihood of Extramarital Affairs (Scientific Journal of Research Studies in Future Psychology, 2025)
In the digital era, social media platforms have redefined the boundaries of emotional and relational intimacy. The present study investigates how social media exposure and online emotional intimacy contribute to the likelihood of extramarital affairs among married adults. Building on attachment theory, self-expansion theory, and emotional regulation frameworks, the research explores the interplay between online interaction frequency, emotional disclosure, and relational satisfaction. Data were obtained from 482 married participants (ages 25–55) recruited through stratified sampling from major metropolitan areas, analyzed using structural equation modeling (SEM). Findings revealed that higher exposure to social media predicted greater online emotional intimacy (β = 0.42, p < 0.001), which, in turn, increased the likelihood of infidelity-related behaviors (β = 0.37, p < 0.001). Emotional intimacy online mediated the relationship between time spent on social media and perceived relational dissatisfaction, partially supporting the compensatory model of virtual connection. Gender differences indicated that men demonstrated higher behavioral risk, whereas women reported stronger emotional displacement effects. Results suggest that social media exposure indirectly heightens the risk of extramarital affairs through intensified emotional engagement and digital proximity. The study underscores the importance of emotional regulation and media literacy interventions in promoting marital resilience in the context of pervasive digital connectivity. The article concludes that while social media facilitates emotional expression, it simultaneously blurs the ethical and affective boundaries sustaining marital fidelity